Cultivo da abóbora maranhão sob dosagens de nitrogênio e lâminas de irrigação diferenciadas. - Bezerra, Rômulo Uchôa (2017)
The objective of this work was to evaluate the effect of irrigation slides, nitrogen doses and their interactions on pumpkin (Cucurbita moschata) cultivation. The experiment was conducted at the Meteorological Station of the Federal University of Ceará (UFC), from September to November 2016. The experimental design was a completely randomized design with subdivided plots, and the treatments were composed of four levels of nitrogen fertilization (50 (50, 75, 100, 125%) of the recommended value, and the combination of four irrigation slides based on evaporation measured in a Class A Two replicates. The cultivar Abóbora Maranhão (jerimum of milk) was used, which was installed in the spacing of 2 x 2 m, irrigated by drip system, with double hose lines, a line with drippers of the same flow rate to apply the fertilizer, and Another line with drippers of 2; 4; 8 L h-1 , combined with each other to provide the slide according to the treatments, spaced according to the spacing of the culture. The number of fruits per plant, fresh fruit mass, fruit dry mass, fruit equatorial diameter, fruit polar length, pulp thickness, soluble solids content (° BRIX), index relative chlorophyll and fruit yield. Irrigation slides and nitrogen fertilization levels significantly inflated all the variables analyzed except for the fruit diameter variable that showed significant isolated value for nitrogen fertilization levels. The maximum productivity was achieved in the blade corresponding to 444.10 mm (122.5% of ECA) and a dose of 33.65 kg ha-1 of N (112.16% of the recommended value of N), with a maximum value of 4269 , 6 kg ha-1. The polar largest diameter was 51.71 cm, achieved in the lamina corresponds to 256 mm (68.44% of ECA) and dose 29.02 kg.ha-1 of N (96.96% of the And the highest fresh fruit mass of 2.20 kg was achieved in the leaf corresponding to 453 mm (125% of ECA) and dose 35.88 kg.ha-1 of N (119.5% Of the recommended value of N